STUDY OF ADVERSE REACTIONS FROM THE USE OF MOLASSES OF SACCHARINE SORGHUM (SORGHUM BICOLOR L. MOENCH) (Fiep Bulletin - online, 2012)
Natural products may contain a variety of substances that can cause adverse physiological effects or decrease the bioavailability of some nutrients. This work aimed to evaluate the presence of possible adverse reactions with the use of co-product of the juice of the stem of the saccharine sorghum (Sorghum bicolor L. Moench). For this purpose we used sorghum molasses 21g once daily for 8 weeks and orally and during the study volunteers were instructed to report any signs or symptoms that may present. It was seen that the product in study was well tolerated with no reported adverse reactions during the study period that could commit its use, amount ingested, suggesting its use as a dietary supplement. it is needed larger studies regarding the use as food with property of health.
Keywords: quality; Bicolor Sorghum; adverse reactions